Attraction points: A new sampling design method to quantify common finches’ population - Lorenzo Marazuela Pinela; Ángel Julián Martín Fernández; Pablo-Luis López-Espí (Ecological Indicators)
Existing methodologies for monitoring bird populations primarily focus on their presence, habitat, physical and health characteristics, and, more comprehensively, their abundance and trends in breeding season. Due to the fact that these methodologies do not use unbiased statistical estimators, the accurate estimation of bird densities or obtaining measures of abundance is often based on indirect counts, such as, detection probability versus distance, or assumptions, such as the homogeneous distribution of all individuals, which are then correlated with bird density. Most of these counts provide a multispecies approximation of long-term trends but may be inaccurate for specific species, regions or outside of the breeding season. In the case of finches (Fringillidae), determining a direct and more accurate estimate of density of their populations in a specific area requires a specialised methodology based on unbiased statistical estimators, one that accounts on the unique characteristics of these birds and minimises the issues associated with commonly applied multispecies methodologies.Currently, no quantitative population management method exists that enables wildlife managers to ensure the sustainable management of finch populations in a specific territory throughout their annual life cycle. As part of the development of a quantitative method for this purpose, this study introduces a population inventory model based on fixed points utilising live decoy birds of the fringillid species being inventoried. The model leverages the ethological characteristics of this bird family, which are non-territorial and seeks the company of conspecifics, which they attract through song. Consequently, its applicability is limited to other bird taxa with similar behavioural traits.The “Attraction Points Method” (APM), which uses the songs of live congeners, as described here, has been employed and evaluated in several projects for tracking finch populations in Spain, particularly in the Community of Madrid, where a continuous study of their populations has been conducted since 2018. The study was planned in three periods: the beginning and end of the breeding season (pre-nuptial and post-nuptial), and wintering, allowing for the calculation of survival, mortality and reproductive success ratios.This article presents the model, the results obtained from its application, and its advantages and disadvantages for the control and sustainable management of fringillid populations compared to other frequently used sampling models.